Volume 2: Pipeline Integrity Management 2012
DOI: 10.1115/ipc2012-90484
|View full text |Cite
|
Sign up to set email alerts
|

ILI Based Dent Screening and Strain Based Analysis

Abstract: Pipeline operators often deal with the large numbers of dents that require further consideration, and are required to prioritize these dents for further investigation and repair. Code guidance is clear on the relative severity of dents based on a depth or associated with welds, corrosion, gouging or cracking. It allows the pipeline operators to prioritize their dig lists and limit the number of “investigative digs” by omitting plain and shallow dents. However, the dent depth criterion has limitations, experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Although pipeline integrity assessment has gained achievements in the pipeline industry practices, there is still a lack of a process from data collection to model establishment of the pipeline integrity assessment [3] . In recent years, there are many studies focus on dent assessment with ILI data and FEM analysis, such as the studies done by Katina Tinacos [4] , Race J M [5] , Lei Z [6,7] , Xian-Kui Zhu [8] and Brian Leis [9] . But these studies did not establish the modeling of the pipe based on ILI data in the FEM simulation and strain analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Although pipeline integrity assessment has gained achievements in the pipeline industry practices, there is still a lack of a process from data collection to model establishment of the pipeline integrity assessment [3] . In recent years, there are many studies focus on dent assessment with ILI data and FEM analysis, such as the studies done by Katina Tinacos [4] , Race J M [5] , Lei Z [6,7] , Xian-Kui Zhu [8] and Brian Leis [9] . But these studies did not establish the modeling of the pipe based on ILI data in the FEM simulation and strain analysis.…”
Section: Introductionmentioning
confidence: 99%
“…A strain-based criteria based on ASME B31.8 calculations is used instead of the dentdepth based assessment for dent assessment [4]. Strain based dent assessment consists of calculating bending strains in circumferential and longitudinal direction and longitudinal extensional strain of the pipeline.…”
Section: Dent Assessment Of Pipelinesmentioning
confidence: 99%
“…Strain based dent assessment consists of calculating bending strains in circumferential and longitudinal direction and longitudinal extensional strain of the pipeline. It has been identified that the strains calculated by ASME B31.8 formulas are twice the actual strains induced in the pipeline [4], [5]. The corrected ASME B31.8 equations for calculating circumferential bending strain and longitudinal bending strain are as follows [4], [5], [6]:…”
Section: Dent Assessment Of Pipelinesmentioning
confidence: 99%
See 2 more Smart Citations